Estado e patrimônio cultural: a memória da hidrovia do Rio Iguaçu (PR) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The implementation of steam navigation on the Iguaçu River, between the years 1882 and 1953, contributed to the formation, occupation and development of several cities distributed along the navigable stretch of this river that, in the state of Paraná, comprises from the Port of Caiacanga - which today belongs to the municipality of Porto Amazonas - to the Port of Salto - a town that gave birth to the municipality of Porto Vitória. The use of this mode of transportation contributed to the economic cycles of yerba mate and wood, constituting with the railroad the Complex Exporter of Traditional Paraná, that allowed the products extracted in the region to reach the coast of Paraná with destiny to export. However, due to factors such as the improvement of land transport - with the construction of highways - and the decay of the economy, the waterway declined and was deactivated in the 1950s. The expansion of the circulation of goods and passengers, functioning of the waterway also provided local and regional social and cultural development and, consequently, the constitution of the cultural heritage of cities formed along its route. The present research had the objective of analyzing the performance of the municipal public authorities on the cultural heritage of the Iguaçu river waterway (PR), in Paraná municipalities of Porto Amazonas, São Mateus do Sul, União da Vitória and Porto Vitória. To do so, we sought to identify this cultural heritage in the cities surveyed, as well as to ascertain its conservation status and uses. The conception of cultural heritage adopted in the research contemplates, not only the assets and practices endorsed and institutionalized by the State, through instruments of protection such as toppling and registration, but everything that can represent and reinforce the memory of a given period, here represented by river navigation on the Iguaçu River. Considering the distribution of competences among the different scales of political action in Brazil (federal, state and municipal), propitiated by the structure imposed by the Federal Constitution of 1988, it was observed that actions undertaken by municipal public authorities are essential for the preservation of cultural heritage local, actions that must be conducted in order to support the recognition of this heritage by the local population, going beyond actions such as tipping and registration. Therefore, it was observed that this issue demands greater commitment from the local public power and the effectiveness of collaboration between the different scales of political action.
Keywords: memória social.; patrimônio cultural; poder público; social memory; cultural heritage; public power; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA